Peningkatan Literasi Ekonomi Syariah Masyarakat melalui Sosialisasi Akad Salam pada Transaksi Online - Yusuf, Yusuf (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service activity aims to enhance the Islamic economic literacy of the people in Ciawigajah Village, Beber District, Cirebon Regency, through socialization and training on the application of Salam contracts in online transactions. The program was motivated by the community’s limited understanding of Islamic business principles (muamalah), particularly in digital-based trade practices. The implementation method used a participatory approach through interactive socialization, group discussions, and simulations of Salam contract applications within online business contexts. The results of the activity showed a significant increase in participants’ understanding of the concepts and practical implementation of Salam contracts, with several local MSME actors beginning to apply the pre-order system based on Islamic principles. The impact of this activity was not only observed in terms of increased knowledge but also in behavioral changes toward more transparent, fair, and Sharia-compliant economic transactions. For program sustainability, continuous mentoring for MSME actors is recommended, along with the development of technology-based digital learning materials and collaboration among universities, village governments, and Islamic financial institutions to strengthen the local digital Sharia economic ecosystem. This activity is expected to serve as a model for Sharia economic empowerment based on literacy and digitalization that can be replicated in other regions, fostering the values of justice, honesty, and blessing within rural communities.